2020
DOI: 10.1109/tvt.2020.3025371
|View full text |Cite
|
Sign up to set email alerts
|

Improper Gaussian Signaling for Computationally Tractable Energy and Information Beamforming

Abstract: The transmit time-switching (transmit-TS) approach, under which the energy and information are transferred over different fractions of a time slot has proved its supremacy over the power splitting (PS) approach of simultaneous wireless information and power transfer, where PS splits the power of the received signal for energy harvesting and information decoding. For integrating data and energy transfer, this paper develops new classes of beamforming that are suitable for improper Gaussian signaling which is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…RIS can modulate the channels, thus providing another degree-of-freedom to improve the coverage and/or manage interference. The papers [31], [33], [34], [36], [39]- [41] showed that RIS can improve the performance of singlecell and/or multi-cell BCs. The paper [42], [43] showed that RIS can enlarge the rate region of the K-user multiple-input, single-output (MISO) ICs.…”
Section: A Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…RIS can modulate the channels, thus providing another degree-of-freedom to improve the coverage and/or manage interference. The papers [31], [33], [34], [36], [39]- [41] showed that RIS can improve the performance of singlecell and/or multi-cell BCs. The paper [42], [43] showed that RIS can enlarge the rate region of the K-user multiple-input, single-output (MISO) ICs.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…In addition to RS and RIS, there are other interferencemanagement tools such as improper Gaussian signaling (IGS) [39], [46]- [69]. In a zero-mean proper complex Gaussian signal, the real and imaginary parts of the signal are independent and identically distributed (iid).…”
Section: A Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Explicitly, this is regarded as improper Gaussian signaling (IGS) in contrast to the proper Gaussian signaling (PGS) scheme of ( 14), which has been shown to enhance the throughput of severely interference-limited networks [34]- [36] . The reader is also referred to [37] for another instantiation of IGS based (traditional) RZFB.…”
Section: A Igs Problem Statementmentioning
confidence: 99%
“…• Like in [27], here we also use improper Gaussian signaling (IGS) in the BS signal transmission, which has been shown to substantially improve the users' max-min rates (see e.g. [28]- [32]) thanks to its ability to mitigate the severe interferences in interference-limited systems. The performance gap between IGS and conventional proper Gaussian signaling (PGS) becomes substantially wider under more severe interference regimes.…”
Section: Introductionmentioning
confidence: 99%